#### Answer

$x=-\frac{1}{a}$

#### Work Step by Step

We factor:
$a^{2}x^{2}+2ax+1=0$
$(ax+1)^{2}=0$
$ax+1=\sqrt{0}=0$
$ax=-1$
$x=-\frac{1}{a}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$x=-\frac{1}{a}$

We factor:
$a^{2}x^{2}+2ax+1=0$
$(ax+1)^{2}=0$
$ax+1=\sqrt{0}=0$
$ax=-1$
$x=-\frac{1}{a}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.